Simplexity : simplifying principles for a complex world - Berthoz, A. (Editions Odile Jacob Book., 2012)
"In this book a noted physiologist and neuroscientist introduces the concept of simplexity, the set of solutions living organisms find that enable them to deal with information and situations, while taking into account past experiences and anticipating future ones. Such solutions are new ways of addressing problems so that actions may be taken more quickly, more elegantly, and more efficiently. In a sense, the history of living organisms may be summed up by their remarkable ability to find solutions that avoid the world's complexity by imposing on it their own rules and functions. Evolution has resolved the problem of complexity not by simplifying but by finding solutions whose processes--though they can sometimes be complex--allow us to act in the midst of complexity and of uncertainty. Nature can inspire us by making us realize that simplification is never simple and requires instead that we choose, refuse, connect, and imagine, in order to act in the best possible manner. Such solutions are already being applied in design and engineering and are significant in biology, medicine, economics, and the behavioral sciences"--